2022
DOI: 10.1002/jcph.2108
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressants and Antipsychotics in Human Pregnancy: Transfer Across the Placenta and Opportunities for Modeling Studies

Abstract: There is limited information about the transfer of antidepressants and antipsychotics across the human placenta. The objective of the current review was to systematically screen the scientific literature using relevant keywords to collect quantitative data on placental transfer of these drugs in humans and to give an overview of current modeling approaches used in this context. The collected data encompassed clinically measured fetal:maternal (F:M) concentration ratios (ie, the ratio between drug concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 107 publications
(266 reference statements)
0
4
0
Order By: Relevance
“…Similar to non-pregnant adults, maternal exposure to sertraline is marked by interindividual variability likely derived from genetic variation in CYP2C19(48, 5058, 6062, 64, 65). Placental transfer of sertraline ranges between 30-40%(5153, 5557, 61, 65, 66). These pharmacokinetic findings imply that, to maintain sufficient maternal exposures, sertraline doses should not be reduced during pregnancy and may even have to be increased for certain women in the second or third trimester depending on their clinical response. Pharmacodynamics Our understanding of the influence of pregnancy on sertraline efficacy is insufficient to inform antenatal dosing.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to non-pregnant adults, maternal exposure to sertraline is marked by interindividual variability likely derived from genetic variation in CYP2C19(48, 5058, 6062, 64, 65). Placental transfer of sertraline ranges between 30-40%(5153, 5557, 61, 65, 66). These pharmacokinetic findings imply that, to maintain sufficient maternal exposures, sertraline doses should not be reduced during pregnancy and may even have to be increased for certain women in the second or third trimester depending on their clinical response. Pharmacodynamics Our understanding of the influence of pregnancy on sertraline efficacy is insufficient to inform antenatal dosing.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, cell lines derived from human choriocarcinoma can effectively stimulate the endocrine activities of human trophoblasts [ 33 , 34 ]. In addition, it is considered quite easy to obtain a sufficient simulation of the placental barrier from placental choriocarcinoma cell lines, such as BeWo, Jar, and JEG-3, by permitting cells to construct both monolayers and multiple layers [ 35 , 36 , 37 ]. Indicatively, an in vitro study utilizing the BeWo cell line showed that synthetic cannabinoids can lead to apoptosis and mitochondrial dysfunction in placental cells, thus leading to disturbances in fetus health [ 38 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…The limitations mentioned above primarily stem from the distinct structural and functional differences between the human placenta and those of other mammals [ 35 , 36 , 37 , 38 ]. The human placental barrier comprises a single layer of multinucleated cells known as syncytiotrophoblasts.…”
Section: Resultsmentioning
confidence: 99%
“…Throughout pregnancy, women may suffer from many other psychiatric disorders, such as bipolar disorder, post-partum depression, eating disorders, obsessive–compulsive disorder, posttraumatic stress disorder, panic attacks, and puerperal psychosis (McIntyre et al 2022 ; Ortega et al 2023 ). However, peripartum mental illnesses are largely under-diagnosed, and often undertreated (Marcus et al 2003 ), specially due to the risk of adverse effects of psychiatric drugs on the fetus (harelip, cleft palate, floppy infant, Ebstein’s anomaly, cardiac, lung and kidney alterations), teratogenicity and fetal toxicity, as well as to the possible increase of side effects in the mother (Mesches et al 2020 ; Wang et al 2022 ; Zheng et al 2022 ). Other reasons might include the following: the lack of specialized mental health during pregnancy resources, the poor connection between gynecology and mental health services (World Health Organization 2022 ), as well as the reluctance of partners and family members to recognize and respond to mothers’ emotional and practical needs (Dennis and Chung-Lee 2006 ).…”
Section: Introductionmentioning
confidence: 99%